Desenvolvimento de queijo tipo prato com reduzido teor de sal (NaCl) e adição de algas marinhas - Jiménez, Maximiliano Segundo Escalona (2014)
Salt (NaCl) is the principal sodium (Na) supplier in the diet; their excess intake is associated with hypertension and other diseases. Salt is also one of the most important ingredients in cheese making, therefore it is not recommended its total replacement. The aim of this work was to develop the Prato cheese with salt reduced and adding seaweed (Laminaria digitata and Ascophyllum nodosum). The approximately composition and mineral content of seaweeds were determinate. For each one seaweed, four formulations were prepared (TL for L. digitata and TA for A. nodosum), and their composition, hardness, gumminess and sensorial acceptance were determined. Mineral content was quantified in one treatment of each seaweed (both TL4, TA4 with 70% of salt and 70% of seaweed), and compared with commercial Prato cheese (CPC). From the best formulation, a second experiment was planned with 12 treatments. Physical-chemical composition, hardness and gumminess in 12 treatments were determined. The pH and proteolysis was monitored for 60 days. Na content was quantified in six treatments (04 axial points, central point and 01 control) and treatments were subjected to an acceptance test and ranking test. L. digitata recorded higher contents of minerals, protein and moisture (P<0.05), however A. nodosum had higher content of total dietary fiber and total lipids. Ca, K, and Na was significantly higher in L. digitata (P <0.05), while Mg was greater in A. nodosum. The TL4 treatment showed higher Ca content, while TA4 recorded higher content of Zn compared to the commercial Prato cheese. Ashes, titratable acidity and hardness were majority affected by seaweed addition. The consumption intention test favored treatment TL1 for cheeses with L. digitata and TA2 for cheeses of A. nodosum. In the second study, changes in the levels of chloride, sodium and ash were influenced by seaweed addition. The pH variation during storage and parameters of hardness and gumminess were affected by the salt concentration. The proteolytic activity was higher in treatments with lower levels of salt and seaweed. The salt content was determining the attributes of flavor, salt level and overall appearance. The central point treatment was the most widely accepted. Nutritional and technological properties of seaweed can be used in the manufacture of Prato cheese type with reduced salt content, improving some physico-chemical and textural characteristics without compromising its quality.